2022
DOI: 10.1111/exd.14641
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model of cutaneous T‐cell lymphoma revealed the combined effect of mogamulizumab with psoralen and ultraviolet a therapy

Abstract: Mycosis fungoides (MF) is a subtype of cutaneous T‐cell lymphoma (CTCL). Topical or systemic treatment with psoralen, such as 8‐methoxypsoralen (8‐MOP), followed by ultraviolet A (UVA) irradiation (PUVA therapy) is an effective phototherapy for early‐stage MF. However, the efficacy of PUVA therapy for advanced‐stage MF is not satisfactory, and the ideal combination partner for PUVA therapy has not yet been found. In this study, we developed a new mouse model of CTCL in which efficacy of PUVA was detected and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Most notably, analogs A75-A77 demonstrated an enhanced ability to induce RXR homodimerization (Figure 2B), activate RXRE (Figure 3B), and reduce CTCL cell proliferation (Figure 4) relative to bexarotene. The results suggest that these compounds, if tested with in vivo CTCL animal models [40][41][42][43][44], may produce more satisfactory outcomes in CTCL disease remission. However, A77 was cytotoxic at the lowest concentration evaluated, so additional testing is warranted before moving onto a mouse model.…”
Section: Discussionmentioning
confidence: 95%
“…Most notably, analogs A75-A77 demonstrated an enhanced ability to induce RXR homodimerization (Figure 2B), activate RXRE (Figure 3B), and reduce CTCL cell proliferation (Figure 4) relative to bexarotene. The results suggest that these compounds, if tested with in vivo CTCL animal models [40][41][42][43][44], may produce more satisfactory outcomes in CTCL disease remission. However, A77 was cytotoxic at the lowest concentration evaluated, so additional testing is warranted before moving onto a mouse model.…”
Section: Discussionmentioning
confidence: 95%
“…The “nude” (nu/nu) mouse model, which lacks a mature thymus due to a Foxn1 gene mutation, resulting in underdeveloped T cells ( Kaushik et al, 1995 ), has become a critical model for evaluating CTCL therapies, especially in terms of treatment responses for MF patient-derived skin lesions. These mice with transplants of MF have shown superior responses to combination therapies like PUVA and mogamulizumab, a monoclonal antibody targeting CCR4, compared to monotherapies ( Thaler et al, 2004 ; Nakahashi et al, 2022 ). Studies using “nude” mice highlight the potential of Vorinostat and the HIF-1α inhibitor Echinomycin in CTCL management ( Wang et al, 2020 ; Xia et al, 2020 ).…”
Section: Transplantation Mouse Models In Ctcl Researchmentioning
confidence: 99%
“…Cutaneous T-cell lymphoma (CTCL) is caused by the clonal proliferation of T lymphocytes originating in the skin and is a type of extranodal non-Hodgkin lymphoma. Psoralen with ultraviolet A (PUVA) phototherapy is a common treatment strategy for CTCL in clinical settings ( 145 , 146 ). A study demonstrated that USP2 is expressed in both quiescent and activated T lymphocytes, and its expression is significantly reduced in advanced CTCL.…”
Section: Targeting Usp2 For Cancer Therapymentioning
confidence: 99%